2019
DOI: 10.1002/mds.27595
|View full text |Cite
|
Sign up to set email alerts
|

Sample enrichment for clinical trials to show delay of onset in huntington disease

Abstract: Background Disease‐modifying clinical trials in persons without symptoms are often limited in methods to assess the impact associated with experimental therapeutics. This study suggests sample enrichment approaches to facilitate preventive trials to delay disease onset in individuals with the dominant gene for Huntington disease. Methods Using published onset prediction indexes, we conducted the receiver operating curve analysis for diagnosis within a 3‐year clinical trial time frame. We determined optimal cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…This is not an uncommon problem in HD, and most studies (including clinical trials) target individuals that are either premanifest or early in the disease process. [58][59][60] Potential strategies to help mitigate loss to follow-up can include engaging advocacy groups, participation in HD community events, and engagement of social media. 61,62 Given that individuals with more severe disease were more likely to discontinue participation as a result of worsening symptoms (and in many cases the inability to provide informed consent at a later study visit) and that these individuals are precisely the individuals who are experiencing the largest declines in health, we would expect this to negatively impact our findings such that effect sizes are smaller than would be expected for the HD population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not an uncommon problem in HD, and most studies (including clinical trials) target individuals that are either premanifest or early in the disease process. [58][59][60] Potential strategies to help mitigate loss to follow-up can include engaging advocacy groups, participation in HD community events, and engagement of social media. 61,62 Given that individuals with more severe disease were more likely to discontinue participation as a result of worsening symptoms (and in many cases the inability to provide informed consent at a later study visit) and that these individuals are precisely the individuals who are experiencing the largest declines in health, we would expect this to negatively impact our findings such that effect sizes are smaller than would be expected for the HD population.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the participants with more advanced disease were more likely to be lost to follow‐up, and differential attrition may have made it more difficult to identify significant declines in physical HRQOL. This is not an uncommon problem in HD, and most studies (including clinical trials) target individuals that are either premanifest or early in the disease process . Potential strategies to help mitigate loss to follow‐up can include engaging advocacy groups, participation in HD community events, and engagement of social media .…”
Section: Discussionmentioning
confidence: 99%
“…We iteratively performed joint estimations of these population parameters with the individual ones to minimize errors between the idealized curves and the individual projections. 11 The result is called HD COURSE MAP.…”
Section: Multimodal Digital Model Of Disease Progression (Hd Course Map)mentioning
confidence: 99%
“…Still, Paulsen and colleagues showed that they could identify populations most likely develop the disease within three years, using Multivariate Risk Score (MRS), and to a lesser extent the PIN. 11 Further, Langbehn and colleagues show that the PIN index can increase the effect size of hypothetical treatments for a range of possible clinical endpoints in addition to disease onset. 12 This property of the PIN index is only incidental, however, since PIN has been computed to predict clinical onset, not the progression of particular biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have shown that immune and mitochondrial dysfunction, systemic toxicity, and protein degradation are important mechanisms for HD pathophysiology (Figure 3) [15][16][17][18]. The first symptoms are usually noted between 35 and 45 years of age and death typically appears within 15-20 years after the initial diagnosis.…”
Section: Pathophysiology Of Hdmentioning
confidence: 99%